Patient-centered interprofessional education in cancer care: a systematic scoping review - Tobias Fragner; Honja Hama; Adis Šerifović; Kathrin Kirchheiner; Igor Grabovac (BMC Medical Education)
Abstract Background Cancer remains a critical global health issue requiring a comprehensive interdisciplinary approach for effective treatment. Interprofessional education (IPE) is essential for overcoming barriers to collaboration among healthcare professionals and fostering efficient teamwork in cancer care. Objective This systematic scoping review aims to explore the role of IPE in enhancing interprofessional collaboration within cancer care by mapping and synthesizing the implementation, impact, and evaluation strategies of patient-centered IPE programs in this field. Methods A comprehensive search was conducted across seven databases, including CENTRAL, CINAHL, Embase, MEDLINE, PsycInfo, Scopus, and Web of Science, from their inception to January 2024. Grey literature was also sought through online sources and by contacting relevant organizations. Data were extracted and synthesized narratively following a standardized protocol. Results Seven studies met the inclusion criteria, highlighting various educational methods such as web-based platforms, face-to-face interactions, experiential learning, and simulation-based training. Patient-centered IPE programs notably improved interprofessional collaboration, communication, knowledge, and self-confidence among healthcare professionals. Additionally, several programs led to concrete changes in clinical practice and institutional policies. Evaluation strategies primarily utilized established frameworks such as Kirkpatrick’s model and Moore’s outcome levels to assess multiple layers of outcomes, including participant satisfaction, knowledge acquisition, competence, and behavior change. Conclusions The findings indicate that patient-centered IPE programs effectively promote interprofessional collaboration and enhance clinical competencies in cancer care. Future research should focus on long-term evaluations, address systemic barriers, expand geographical scope, and utilize standardized evaluation frameworks to further improve the design and implementation of patient-centered IPE programs in cancer care.